A purification process for heparin and precursor polysaccharides using the pH responsive behavior of chitosan. (16th July 2015) - Bhaskar, Ujjwal; Hickey, Anne M.; Li, Guoyun; Mundra, Ruchir V.; Zhang, Fuming; Fu, Li; Cai, Chao; Ou, Zhimin; Dordick, Jonathan S.; Linhardt, Robert J.
<x xml:space="preserve">Abstract</x> The contamination crisis of 2008 has brought to light several risks associated with use of animal tissue derived heparin. Because the total chemical synthesis of heparin is not feasible, a bioengineered approach has been proposed, relying on recombinant enzymes derived from the heparin/HS biosynthetic pathway and Escherichia coli K5 capsular polysaccharide. Intensive process engineering efforts are required to achieve a cost‐competitive process for bioengineered heparin compared to commercially available porcine heparins. Towards this goal, we have used 96‐well plate based screening for development of a chitosan‐based purification process for heparin and precursor polysaccharides. The unique pH responsive behavior of chitosan enables simplified capture of target heparin or related polysaccharides, under low pH and complex solution conditions, followed by elution under mildly basic conditions. The use of mild, basic recovery conditions are compatible with the chemical N‐deacetylation/N‐sulfonation step used in the bioengineered heparin process. Selective precipitation of glycosaminoglycans (GAGs) leads to significant removal of process related impurities such as proteins, DNA and endotoxins. Use of highly sensitive liquid chromatography‐mass spectrometry and nuclear magnetic resonance analytical techniques reveal a minimum impact of chitosan‐based purification on heparin product composition. © 2015 American Institute of Chemical Engineers Biotechnol. Prog., 31:1348–1359, 2015